The Antimicrobial effect of a cyclic peptide Nostophycin isolated from wastewater cyanobacteria, Nostoc calcicola - Gupta, Vaishali; Vyas, Deepak (Current Botany, 2021)
Different types of peptides are produced by cyanobacteria of the genus Nostoc, which are unique in structure and have a wide spectrum of biological activities. The objective of the study to explore different habitats of organism and study antimicrobial activities to improve their pharmaceutical application and drug like properties by structure modification. A cyclic peptide nostophycin was isolated from Nostoc calcicola (MK506349) through freeze dried lyophilization method. Its structure has been elucidated with FT-IR, 1HNMR, 13CNMR and LC-MS. Glycine, d-glutamine, l-phenylamine, d-isoleucine, l-proline and a novel amino acid Ahoa are constituents of nostophycin. 1HNMR, 13CNMR spectroscopy confirmed the number of protons and carbons, and characteristics peak determined the structure and fragmentation pattern through LCMS. Nostophycin possess Ahoa instead of Adha which makes it different from microcystin. Nostophycin exhibits antimicrobial activity against E.coli, S. aureus, C. albicens and A. niger. A good antifungal activity (9-52 μg/mL) and moderate antimicrobial activity (concentration 18-52 μg/mL) were found for nostophycin. In case of already known peptides, these molecules may be further exploited to improve pharmaceutical application and future drug development.